‘Student-Developed Case Studies: An Experiential Approach for Teaching Ethics in Management’ - Laditka, Sarah B. (Journal of business ethics, 2006)
To prepare for ethically challenging situations in the workplace, it is useful for students to explore their attitudes toward ethical issues and their own value systems. An experiential assignment to teach ethics in business programs is presented. This method allows instructors to incorporate a “stand alone” assignment in ethics into a course that focuses on another area in management. The assignment, student-developed case studies of ethical situations in the workplace, requires students to develop individual case studies in ethics drawing on their workplace experiences to illustrate ethical principles. The assignment requires students to describe an ethical situation they encountered in the workplace, their relevant value systems, sources of information consulted, their role in the organization, and how they resolved the ethical situation, considering how their experiences since the time of the situation might influence analogous decision making today. To assess student learning, we used thematic analysis to evaluate the content of the case studies, and descriptive statistics to analyze responses to a post-assignment survey. Based on our analysis of the content of the case studies and student responses, this appears to be an effective learning tool to actively engage students in a consideration of, and discussion about, ethical issues in management, and to learn from the experiences of others.